Exploring a Water–Ethyl Acetate System for the Efficient Synthesis of 4‐Aryl Quinolines - Mohammad Qandalee; Aliyeh Khajeh‐Khezri; Mohammad Alikarami; Silvia Izquierdo; Ignacio M. López‐Coca (ChemistryOpen)
Heterocyclic compounds, particularly aryl quinolines, are of paramount importance in pharmaceuticals, materials science, and agrochemicals owing to their diverse biological and physicochemical properties. However, traditional synthesis methods often rely on organic solvents and catalysts, which raise environmental and health concerns while requiring high energy inputs. This study addresses these challenges by applying the principles of green chemistry to develop a sustainable, efficient, and environmentally friendly synthetic route for aryl quinolines.